The framework for learning using video based on cognitive load theory among visual learners - Nurul 'Izzati Hamizan, 1990- , author 587504; Norah Md. Noor, supervisor 249239; Fakulti Pendidikan 8185 (2013)
Project Paper (Sarjana Muda Sains dan Komputer serta Pendidikan (Fizik)) - Universiti Teknologi Malaysia, 2013